1995
DOI: 10.1007/bf02443698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylates on the toxicity of GABA-lytics in mice

Abstract: Preliminary injection of aspirin and salicylic acid increases the toxicity of picrotoxin, but not of bicuculline. Aspirin inhibits binding of 3H-diazepam and N-methyl-3H -methylphenazepam with membranes from the brain of intact mice. In view of the fact that salicylates reduce the content and sorption capacity of serum albumin, this protein can be assumed to be involved in the detoxieation of picrotoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Previous studies have indicated that during the development of allergen-induced airway responses, activation of PI3K/Akt leads to an increase in IL-13 that in turn, activates the airway epithelial cell (AEC) GABAergic system which acts in autocrine and paracrine fashions to enhance mucus hypersecretion of AECs resulting to airway obstruction (Corry & Kheradmand, 2007;Lu & Inman, 2009). In another study, it has been found that aspirin is involved in the detoxification of GABA-lytic picrotoxin (PT), an antagonist for the GABA A receptor chloride channels (Golovko et al, 1995). The inhibition of picrotoxin by aspirin restores GABA activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that during the development of allergen-induced airway responses, activation of PI3K/Akt leads to an increase in IL-13 that in turn, activates the airway epithelial cell (AEC) GABAergic system which acts in autocrine and paracrine fashions to enhance mucus hypersecretion of AECs resulting to airway obstruction (Corry & Kheradmand, 2007;Lu & Inman, 2009). In another study, it has been found that aspirin is involved in the detoxification of GABA-lytic picrotoxin (PT), an antagonist for the GABA A receptor chloride channels (Golovko et al, 1995). The inhibition of picrotoxin by aspirin restores GABA activity.…”
Section: Introductionmentioning
confidence: 99%
“…However, a good number of the patients with AERD were recruited from the outpatient clinics of the experienced pulmonologists in Japan. Interestingly, aspirin has been shown to be involved in the detoxification of GABAlytic picrotoxin, an antagonist for GABA type A receptor [28]. The inhibition of picrptoxin by aspirin restores GABA activity, suggesting such interactions with aspirin might be present in pathobiology of AERD.…”
Section: Discussionmentioning
confidence: 99%
“…So, modification of cysteine and replacing the guanidine group with a urea linkage in the side chain of arginine could be a risk factor for aspirin hypersensitivity in asthmatics. Interestingly, it has been reported that the extraneuronal GABAergic system might to be implicated in the mechanisms of AERD [108], and aspirin has been shown to be involved in the detoxification of GABAlytic picrotoxin, an antagonist for GABA type A receptor [112]. The inhibition of picrotoxin by aspirin restores GABA activity, suggesting such interactions with aspirin might be present in AERD patients.…”
Section: Solute Carrier Family 6 Member 12 (Slc6a12) Genesmentioning
confidence: 99%